Exploring body mass index and gender-based self-esteem differences in Saudi Arabia - Maaidah Algamdi (Frontiers in Public Health)
BackgroundSelf-esteem (SE) and obesity have been associated in various studies. This study investigates this relationship among adults in Saudi Arabia. The objectives of this study are to investigate the relationships between SE and body mass index (BMI) and to examine the interactions between sociodemographic-related factors.MethodsWe designed a cross-sectional study using an online survey that included sociodemographics, a BMI measure, and the Rosenberg Self-Esteem Scale.ResultsLevels of SE did not change substantially between the various age groups, as indicated by the Chi-Square test X2 (12, N = 332, = 5.278, p-value = 0.948). The results for males reveal that there is a variation in the levels of SE across the different BMI categories. This suggests that the BMI categories have a major influence on the levels of SE among males. In both genders, the results indicate a negative association between variables, with a higher BMI being associated with a lower level of SE. The significance of this association stands for both genders (p-value <0.001). For males, the association has a greater influence (Estimate = −0.110, p-value <0.001) than it does for females (Estimate = −0.099, p-value <0.001). In females, the negative link is larger for education (−0.273) and highly impactful (p-value <0.001) in comparison to men (Estimate = −0.157, p-value <0.001). Higher education levels are associated with a lower BMI (p-value = 0.018). For men, the indirect effects show that education (Estimate = 0.0173*) and marital status (Estimate = −0.0405*) significantly influence SE, with other factors mediating these effects. Both genders experience significant and detrimental impacts from BMI on SE, with males experiencing a more pronounced impact. There are considerable disparities in the ways in which these parameters impact SE in both genders, as revealed by the comparisons of the nested models.ConclusionThere is a negative correlation between BMI and SE in both genders, with a more pronounced impact in men. Gender-specific differences in the relationship between BMI and SE underscore the importance of considering distinct pathways for males and females in future analyses.